Peach: Physico-Chemical characteristics and Bioactive Compounds Content (Research, Society and Development, 2020)
Originating in China, the peach was one of temperate climate species that soon expanded worldwide, and it was also considered a symbol of longevity. Few fruit species have adapted to such diverse climatic situations. Although most producing regions is between latitudes 30º N and 45° S, the peach tree is one of the most important fruit crops in temperate climate explored in Brazil. As other fruits, peach contain bioactive compounds, but still little has been studied about them. Therefore, the aim of this study was to evaluate the physicochemical characteristics, focusing on the composition of bioactive compounds, in peach cultivars used in processing industries in the southern region of RS. Therefore, three cultivars of peaches from two seasons 2008/2009 and 2009/2010 were chosen; Santa Aurea, Esmeralda and Maciel. All fruit were obtained from producers of Pelotas / RS, and cultivated by the tracking system of the fruit. Titratable acidity (AT), pH, soluble solids (SS), SS / AT, total carotenoids, individual carotenoids, total phenolic compounds, individual phenolic compounds and total anthocyanin were evaluated. The results showed that the cultivar Esmeralda presented SS / AT: 20.0 (2008/2009) and the Santa Aurea (2009/2010) a ratio of SS / AT: 17.2. Regarding the acidity, the cultivar that stood out was also the Esmeralda. Cultivar Emerald also showed a higher content of gallic acid in relation to other cultivars in both harvest period. Regarding the content of carotenoids, the Emerald (6.72 mg β-caroteno.100g-1) and Maciel (5.97 mg β- caroteno.100g-1) cultivars showed higher values, both in 2009/2010 harvest.